2019
DOI: 10.3390/sym11040542
|View full text |Cite
|
Sign up to set email alerts
|

New Methodology for Diagnosis of Orthopedic Diseases through Additive Manufacturing Models

Abstract: Our purpose is to develop the preoperative diagnosis stage for orthopedic surgical treatments using additive manufacturing technology. Our methods involve fast implementations of an additive manufactured bone model, converted from CAT data, through appropriate software use. Then, additive manufacturing of the formed surfaces through special 3D-printers. With the structural model redesigned and printed in three dimensions, the surgeon is able to look at the printed bone and he can handle it because the model pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 11 publications
0
11
0
Order By: Relevance
“…FDM techniques can also be used for disease/injury diagnosis purposes. Frizziero et al (2019) 54 reported the use of computed axial tomography (CAT) data which are converted into 3D-printed models, and these models are used to characterize the anatomical structure of fractures and lesions to provide a complete pre-surgery evaluation.…”
Section: Additive Manufacturing Techniques and Processmentioning
confidence: 99%
“…FDM techniques can also be used for disease/injury diagnosis purposes. Frizziero et al (2019) 54 reported the use of computed axial tomography (CAT) data which are converted into 3D-printed models, and these models are used to characterize the anatomical structure of fractures and lesions to provide a complete pre-surgery evaluation.…”
Section: Additive Manufacturing Techniques and Processmentioning
confidence: 99%
“…Medical images were acquired in the Digital Imaging and Communications in Medicine (DICOM) format and transferred to the 3D-printing POC. Three-dimensional digital reconstruction was achieved through a process of image segmentation and conversion in Standard Triangulation Language (STL) format, using open-source software (3D Slicer) [23], according to a well-established procedure in use at our lab [18,24,25] (Figure 2). In accordance with this procedure, the 3D digital reconstruction of the anatomical region of the patient is analyzed and imported in a virtual working environment (Blender) [26] (Figure 3) able to plan and simulate the correction, to design the patient-specific (PS) implants and/or device and to predict the final outcome.…”
Section: Image Acquisition and Reconstruction Of 3d Modelmentioning
confidence: 99%
“…Invesalius is an open-source software for reconstruction of computed tomography and magnetic resonance images. MeshLab and Meshmixer are graphic software used to correct any mesh irregularities [39][40][41][42][43][44]. The process from CT to 3D digital model is illustrated in Figure 5.…”
Section: Computer Aided Surgical Simulationmentioning
confidence: 99%